131k views
14 votes
I am in need of assistance.

I am in need of assistance.-example-1
User Mohikhsan
by
5.7k points

1 Answer

10 votes

Answer:

A. x = 6.08, x = -0.58

Explanation:


  • \displaystyle (2x)/(x-4)-(2x-5)/(x^2-10x+24)=(-3)/(x-6)

1. Factor the denominator.


  • \displaystyle (2x)/(x-4)-(2x-5)/((x-6)(x-4))=(-3)/(x-6)

2. Multiply the leftmost fraction by (x-6)/(x-6) to get common denominators.


  • \displaystyle \Big ( (x-6)/(x-6) \Big ) (2x)/(x-4)-(2x-5)/((x-6)(x-4))=(-3)/(x-6)

3. Simplify.


  • \displaystyle (2x^2-12x)/((x-4)(x-6))-(2x-5)/((x-6)(x-4))=(-3)/(x-6)

4. Combine like terms.


  • \displaystyle (2x^2-14x+5)/((x-4)(x-6))=(-3)/(x-6)

5. Multiply the right side of the equation by (x-4)/(x-4).


  • \displaystyle (2x^2-14x+5)/((x-4)(x-6))=(-3)/(x-6) \Big ( (x-4)/(x-4) \Big )

6. Simplify.


  • \displaystyle (2x^2-14x+5)/((x-4)(x-6))=(-3x+12)/((x-6)(x-4))

7. "Cancel" out the denominators because they are equivalent.


  • 2x^2-14x+5=-3x+12

8. Set the equation equal to 0.


  • 2x^2-11x-7=0

Quadratic formula:


  • \displaystyle x = (-b\pm √(b^2-4ac) )/(2a)

9. Factor using the quadratic formula.


  • \displaystyle x = (-(-11)\pm √((-11)^2-4(2)(-7)) )/(2(2))

10. Multiply and simplify.


  • \displaystyle x = (11 \pm √(177) )/(4)

11. Plug this into your calculator and solve for x.


  • x=6.07603367 \approx 6.08

  • x=-0.57603367 \approx -0.58

The correct answer is A. x = 6.08, x = -0.58.

User Aleksandra Zalcman
by
5.8k points